EXPLORING THE SOCIAL SUSTAINABILITY OF RUBBER FARMERS – INDIVIDUAL FARMERS PERSPECTIVE - Nuanphromsakul, Kajohnjak; Cioca, Lucian Ionel; Chaveesuk, Singha; Chaiyasoonthorn, Wornchanok (My University, 2022)
This research was geared towards analyzing the factors that influence the social sustainability of rubber farmers from an individual perspective. The research was driven by the fact that in Thailand, rubber farmers are still underprivileged and lack knowledge of marketing, finance, technology, business, and economic opportunities. The research adopted a model that evaluated the relationship between study variables with a focus on their effect on social sustainability. A quantitative methodology was adopted, where the data was collected from 436 individual rubber farmers in Thailand. The proposed model and constructs were evaluated using reliability and validity tests and CFA fitness. The data analysis utilizes structural equation modeling. The findings indicated that social sustainability was directly and significantly influenced by brand image and loyalty factors. Additionally, it was found to be indirectly influenced by satisfaction and trust. The research recommended that improvement in the brand image of the rubber farmers in states both locally and internationally would result in increased business sustainability
Keywords: Brand image; Loyalty; Rubber farmers; Satisfaction; Social sustainability; Sustainability